Strategi Corporate Social Responsibility (CSR) PT Inti Ganda Perdana dalam Pemberdayaan Ekonomi Masyarakat Sekitar Perusahaan - Ervina Nur Habibah; Asriyani Sagiyanto; Yan Bastian (Prisani Cendekia, 2026)
This study aims to analyze the communication strategy of Corporate Social Responsibility (CSR) implemented by PT Inti Ganda Perdana in empowering the economic development of surrounding communities. The research focuses on CSR programs directed toward Micro, Small, and Medium Enterprises (MSMEs), particularly the soybean milk MSME PGS202, as part of the company’s commitment to improving community welfare and economic independence. A descriptive qualitative approach was employed in this study, using data collection techniques such as interviews, observation, documentation, and literature review. The data were analyzed using the Four Step Communication Process theory by Cutlip, Center, and Broom, which includes problem identification, planning and programming, action and communication, and program evaluation. The results show that the company has implemented CSR communication strategies through social mapping, stakeholder engagement, structured planning, continuous implementation, and routine monitoring. However, community participation in the planning stage is still limited and tends to be represented by community leaders. Overall, the CSR program has positively contributed to increasing MSME’s capacity, skills, and economic independence, although challenges remain in community participation, communication effectiveness, and business development sustainability.